Hubungan antara minat dan gaya belajar terhadap peningkatan hasil belajar siswa pada materi keanekaragaman hayati kelas VII di SMPIT Assalam - Afrilia, Fera Fernanda; Fitri Rizkiyah; Faruq Haroky; Rizqi Nur Rachmawati; Mona Anju Sansena (Universitas Garut, 2025)
This study aims to determine the relationship between learning interests and learning styles (visual, auditory, and kinesthetic) with the learning outcomes of class VII students of SMPIT Assalam on biodiversity material. The research method used is a quantitative method of correlational research. This study involved all students in class VII of SMPIT Assalam as the research population. The research sample was determined using purposive sampling, so that a sample of 30 students was obtained. Data collection was carried out through a questionnaire to measure learning styles and learning interests, as well as tests to measure learning outcomes. The results of the study showed that (1) Learning interests influenced learning outcomes, with a t-value of 3.690 and a significance of 0.001; (2) Visual, auditory, and kinesthetic learning styles each had a significant influence on learning outcomes, with t-values of 2.760, 3.697, and 6.832, respectively (greater than t-table 2.056); and (3) Learning interest and learning style simultaneously had a significant effect on learning outcomes, with a calculated F-value of 290.243. Based on the results of this study, it is recommended that teachers implement learning methods that are appropriate to students' learning styles and encourage students to increase their learning interests. Keywords: Learning Interest, Learning Style, Learning Outcomes, Biodiversity